Centralized Goal Formation and Systemic Reform - Strike, Kenneth A. (Education Policy Analysis Archives, 1997)
This paper asks whether there are reasonable concerns about liberty raised by standards driven systemic reform. Part I explores three kinds of concerns, students' interests in autonomy and authenticity, academic freedom, and pluralism. Part II explores two ways of conceptualizing the balance between liberty and various public interests, neo-classical economics and contemporary conservative thought. The paper draws two major conclusions about standards driven systemic reform: (1) This picture of reform raises serious questions about liberty. It may be inconsistent with some liberty interests of students. It is likely to pose serious questions about academic freedom and about pluralism. These concerns should make us cautious about systemic reform and should motivate us to a broader discussion of its assumptions and consequences. (2) The best defense of public sector reform efforts against their market oriented competition is one that emphasizes the importance of political goods such as citizenship. However, standards driven reform needs to avoid linkage with any nationalistic form of communitarianism. In order to do this it needs to seek ways to balance the demands for centralized goals and an educational system with an equal concern for local democracy, pluralism and community. A view of standards and accountability that is narrowly focused on clear public interests is crucial. The paper concludes with an argument that we need to focus attention on the question of what makes for good educational communities, a discussion that is not abetted by debating issues of reform in a framework that poses choices between public sector and market approaches.